2018
DOI: 10.1007/s00787-018-1120-5
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of school-based suicide prevention programmes

Abstract: Suicide is one of the leading causes of death among young people globally. In light of emerging evidence supporting the effectiveness of school-based suicide prevention programmes, an analysis of cost-effectiveness is required. We aimed to conduct a full cost-effectiveness analysis (CEA) of the large pan-European school-based RCT, Saving and Empowering Young Lives in Europe (SEYLE). The health outcomes of interest were suicide attempt and severe suicidal ideation with suicide plans. Adopting a payer's perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 18 publications
1
44
0
2
Order By: Relevance
“…Improving caseloads and accessibility of SNs should be considered as research has found identification of at-risk for suicide adolescents is positively correlated with time spent with those trained in identifying at-risk students (Condron et al, 2015). Research has also shown that school-based suicide prevention programs are cost-effective when compared to the estimated cost of over US$1 million for one suicide (Ahern et al, 2018). Investing in SNs for prevention and intervention of suicide is worthwhile to students, schools, families, and communities.…”
Section: Discussionmentioning
confidence: 99%
“…Improving caseloads and accessibility of SNs should be considered as research has found identification of at-risk for suicide adolescents is positively correlated with time spent with those trained in identifying at-risk students (Condron et al, 2015). Research has also shown that school-based suicide prevention programs are cost-effective when compared to the estimated cost of over US$1 million for one suicide (Ahern et al, 2018). Investing in SNs for prevention and intervention of suicide is worthwhile to students, schools, families, and communities.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most of the interventions were provided in collaboration between different societal sectors, such as health care, elderly care, educational sector and labor market. Of the two suicide prevention evaluations, one study (Ahern et al 2018) analyzed three different universal interventions at school, for school pupils, one of which was cost-effective. The second study (Comans et al 2013) evaluated an indicated intervention given to people bereaved by suicide, and was cost-effective.…”
Section: Population Age Groups Type Of Intervention and Arenamentioning
confidence: 99%
“…Results of the nine studies (around 50% of included articles) were considered to have high potential of transferability to the Swedish context (Ahern et al 2018;Anderson et al 2014;Bosmans et al 2014;Buntrock et al 2017;Lewis et al 2017;Philipsson et al 2013;Uegaki et al 2011;van den Berg et al 2011;van Oostrom et al 2010). Only two studies evaluated interventions delivered to Swedish populations (Philipsson et al 2013;Ahern et al 2018). The first evaluated a dance intervention for teenage girls with mental health problems and was cost-effective from a societal perspective.…”
Section: Quality and Transferability To The Swedish Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Delaney et al, for instance, utilize a CEA as evidence in support of initial endoscopy in dyspepsia patients, 16 and mental health studies have commonly included CEAs for decision-making purposes in various interventions, sometimes under the name "probabilistic sensitivity analysis". 17,18 However, Barton et al note that the CEA, despite its widespread use, does not alone provide a path for optimal decision-making as it does not provide insights into the extent of cost-effectiveness. 19 Some have proposed alternative graphical tools to the CEA in response to the challenges associated with interpreting it as a probability of cost-effectiveness within the frequentist paradigm.…”
Section: Introductionmentioning
confidence: 99%